Long-term Outcome of Kasai Operation on Children with Biliary Atresia between 2001-2010 in Namazi Hospital, Shiraz, Iran: - Ghorban nejad, Fatemeh; Dehghani, Seyed Mohsen; Haghighat, Mahmoud; Forootan, Hamid Reza; Bahador, Ali (Galen Medical Journal, 2014)
Background: Biliary atresia is a 100% fatal disorder without any treatment in infants as a leading cause of cirrhosis and Kasai operation, as the only operative choice, which plays a crucial role in increasing their rate of survival. Nonetheless, many patients end up with liver transplantation in the future owing to various inevitable hepatic and biliary problems which do remain after the Kasai operation. In this study, we aimed to assess the prognosis and influential factors on the outcome of this procedure on children attending Shiraz Namazi Hospital. Patients and Methods: A database of medical records of 61 patients (F=41, M=20) with biliary atresia, aged between 30 to 100 days (65.27Â±18 days) at the time of operation, who had undergone the Kasai operation in Shiraz Namazi Hospital from 2001 to 2010 was examined in a retrospective review. Risk factors of failure (death and liver transplantation) were analyzed by Kaplan-Meier test. Results: Age at the operation time, type of atresia, and dilatation of the bile ducts were identified as the risk factors; 29 patients had signs of hepatomegaly, 6 patients had liver transplantation. Among them, 3 survived. Conclusion: Of the patients, 61% with biliary atresia survived for more than 5 years with their native liver while the overall survival rate among 52 patients was 85.30Â±5.96 months. Postoperative care and regular checkups should be considered for all survivors as a lifelong procedure to prevent any possibilities of future hepatic deterioration.